32.9: Difference between revisions

From testwiki
Jump to navigation Jump to search
 
 
Line 14: Line 14:
! scope="col" style="position: sticky; top: 0;" | Numeric<br>Mathematica
! scope="col" style="position: sticky; top: 0;" | Numeric<br>Mathematica
|- style="background: #dfe6e9;"
|- style="background: #dfe6e9;"
| [https://dlmf.nist.gov/32.9.E1 32.9.E1] || [[Item:Q9388|<math>w(z;\mu,0,0,-\mu\kappa^{3}) = \kappa z^{1/3}</math>]]<br><syntaxhighlight lang="tex" style="font-size: 75%; background: inherit;" inline>w(z;\mu,0,0,-\mu\kappa^{3}) = \kappa z^{1/3}</syntaxhighlight> || <math></math> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">w(z ; mu , 0 , 0 , - mu*(kappa)^(3)) = kappa*(z)^(1/3)</pre></div> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">w[z ; \[Mu], 0 , 0 , - \[Mu]*\[Kappa]^(3)] == \[Kappa]*(z)^(1/3)</pre></div> || Skipped - no semantic math || Skipped - no semantic math || - || -
| [https://dlmf.nist.gov/32.9.E1 32.9.E1] || <math qid="Q9388">w(z;\mu,0,0,-\mu\kappa^{3}) = \kappa z^{1/3}</math><br><syntaxhighlight lang="tex" style="font-size: 75%; background: inherit;" inline>w(z;\mu,0,0,-\mu\kappa^{3}) = \kappa z^{1/3}</syntaxhighlight> || <math></math> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">w(z ; mu , 0 , 0 , - mu*(kappa)^(3)) = kappa*(z)^(1/3)</pre></div> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">w[z ; \[Mu], 0 , 0 , - \[Mu]*\[Kappa]^(3)] == \[Kappa]*(z)^(1/3)</pre></div> || Skipped - no semantic math || Skipped - no semantic math || - || -
|-  
|-  
| [https://dlmf.nist.gov/32.9.E2 32.9.E2] || [[Item:Q9389|<math>w(z;0,-2\kappa,0,4\kappa\mu-\lambda^{2}) = z(\kappa(\ln@@{z})^{2}+\lambda\ln@@{z}+\mu)</math>]]<br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>w(z;0,-2\kappa,0,4\kappa\mu-\lambda^{2}) = z(\kappa(\ln@@{z})^{2}+\lambda\ln@@{z}+\mu)</syntaxhighlight> || <math></math> || <syntaxhighlight lang=mathematica>w(z ; 0 , - 2*kappa(,)*0 , 4*kappa(mu)- (lambda)^(2)) = z*((kappa(ln(z)))^(2)+ lambda*ln(z)+ mu)</syntaxhighlight> || <syntaxhighlight lang=mathematica>w[z ; 0 , - 2*\[Kappa][,]*0 , 4*\[Kappa][Mu]- \[Lambda]^(2)] == z*((\[Kappa][Log[z]])^(2)+ \[Lambda]*Log[z]+ \[Mu])</syntaxhighlight> || Translation Error || Translation Error || - || -
| [https://dlmf.nist.gov/32.9.E2 32.9.E2] || <math qid="Q9389">w(z;0,-2\kappa,0,4\kappa\mu-\lambda^{2}) = z(\kappa(\ln@@{z})^{2}+\lambda\ln@@{z}+\mu)</math><br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>w(z;0,-2\kappa,0,4\kappa\mu-\lambda^{2}) = z(\kappa(\ln@@{z})^{2}+\lambda\ln@@{z}+\mu)</syntaxhighlight> || <math></math> || <syntaxhighlight lang=mathematica>w(z ; 0 , - 2*kappa(,)*0 , 4*kappa(mu)- (lambda)^(2)) = z*((kappa(ln(z)))^(2)+ lambda*ln(z)+ mu)</syntaxhighlight> || <syntaxhighlight lang=mathematica>w[z ; 0 , - 2*\[Kappa][,]*0 , 4*\[Kappa][Mu]- \[Lambda]^(2)] == z*((\[Kappa][Log[z]])^(2)+ \[Lambda]*Log[z]+ \[Mu])</syntaxhighlight> || Translation Error || Translation Error || - || -
|- style="background: #dfe6e9;"
|- style="background: #dfe6e9;"
| [https://dlmf.nist.gov/32.9.E3 32.9.E3] || [[Item:Q9390|<math>w(z;-\nu^{2}\lambda,0,\nu^{2}(\lambda^{2}-4\kappa\mu),0) = \dfrac{z^{\nu-1}}{\kappa z^{2\nu}+\lambda z^{\nu}+\mu}</math>]]<br><syntaxhighlight lang="tex" style="font-size: 75%; background: inherit;" inline>w(z;-\nu^{2}\lambda,0,\nu^{2}(\lambda^{2}-4\kappa\mu),0) = \dfrac{z^{\nu-1}}{\kappa z^{2\nu}+\lambda z^{\nu}+\mu}</syntaxhighlight> || <math></math> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">w(z ; - (nu)^(2)* lambda , 0 , (nu)^(2)*((lambda)^(2)- 4*kappa*mu), 0) = ((z)^(nu - 1))/(kappa*(z)^(2*nu)+ lambda*(z)^(nu)+ mu)</pre></div> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">w[z ; - \[Nu]^(2)* \[Lambda], 0 , \[Nu]^(2)*(\[Lambda]^(2)- 4*\[Kappa]*\[Mu]), 0] == Divide[(z)^(\[Nu]- 1),\[Kappa]*(z)^(2*\[Nu])+ \[Lambda]*(z)^\[Nu]+ \[Mu]]</pre></div> || Skipped - no semantic math || Skipped - no semantic math || - || -
| [https://dlmf.nist.gov/32.9.E3 32.9.E3] || <math qid="Q9390">w(z;-\nu^{2}\lambda,0,\nu^{2}(\lambda^{2}-4\kappa\mu),0) = \dfrac{z^{\nu-1}}{\kappa z^{2\nu}+\lambda z^{\nu}+\mu}</math><br><syntaxhighlight lang="tex" style="font-size: 75%; background: inherit;" inline>w(z;-\nu^{2}\lambda,0,\nu^{2}(\lambda^{2}-4\kappa\mu),0) = \dfrac{z^{\nu-1}}{\kappa z^{2\nu}+\lambda z^{\nu}+\mu}</syntaxhighlight> || <math></math> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">w(z ; - (nu)^(2)* lambda , 0 , (nu)^(2)*((lambda)^(2)- 4*kappa*mu), 0) = ((z)^(nu - 1))/(kappa*(z)^(2*nu)+ lambda*(z)^(nu)+ mu)</pre></div> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">w[z ; - \[Nu]^(2)* \[Lambda], 0 , \[Nu]^(2)*(\[Lambda]^(2)- 4*\[Kappa]*\[Mu]), 0] == Divide[(z)^(\[Nu]- 1),\[Kappa]*(z)^(2*\[Nu])+ \[Lambda]*(z)^\[Nu]+ \[Mu]]</pre></div> || Skipped - no semantic math || Skipped - no semantic math || - || -
|- style="background: #dfe6e9;"
|- style="background: #dfe6e9;"
| [https://dlmf.nist.gov/32.9.E4 32.9.E4] || [[Item:Q9391|<math>\beta = 2n</math>]]<br><syntaxhighlight lang="tex" style="font-size: 75%; background: inherit;" inline>\beta = 2n</syntaxhighlight> || <math></math> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">beta = 2*n</pre></div> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">\[Beta] == 2*n</pre></div> || Skipped - no semantic math || Skipped - no semantic math || - || -
| [https://dlmf.nist.gov/32.9.E4 32.9.E4] || <math qid="Q9391">\beta = 2n</math><br><syntaxhighlight lang="tex" style="font-size: 75%; background: inherit;" inline>\beta = 2n</syntaxhighlight> || <math></math> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">beta = 2*n</pre></div> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">\[Beta] == 2*n</pre></div> || Skipped - no semantic math || Skipped - no semantic math || - || -
|- style="background: #dfe6e9;"
|- style="background: #dfe6e9;"
| [https://dlmf.nist.gov/32.9.E5 32.9.E5] || [[Item:Q9392|<math>w(z) = \ifrac{P_{n^{2}+1}(\zeta)}{Q_{n^{2}}(\zeta)}</math>]]<br><syntaxhighlight lang="tex" style="font-size: 75%; background: inherit;" inline>w(z) = \ifrac{P_{n^{2}+1}(\zeta)}{Q_{n^{2}}(\zeta)}</syntaxhighlight> || <math></math> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">w(z) = (P[(n)^(2)+ 1](zeta))/(Q[(n)^(2)](zeta))</pre></div> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">w[z] == Divide[Subscript[P, (n)^(2)+ 1][\[Zeta]],Subscript[Q, (n)^(2)][\[Zeta]]]</pre></div> || Skipped - no semantic math || Skipped - no semantic math || - || -
| [https://dlmf.nist.gov/32.9.E5 32.9.E5] || <math qid="Q9392">w(z) = \ifrac{P_{n^{2}+1}(\zeta)}{Q_{n^{2}}(\zeta)}</math><br><syntaxhighlight lang="tex" style="font-size: 75%; background: inherit;" inline>w(z) = \ifrac{P_{n^{2}+1}(\zeta)}{Q_{n^{2}}(\zeta)}</syntaxhighlight> || <math></math> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">w(z) = (P[(n)^(2)+ 1](zeta))/(Q[(n)^(2)](zeta))</pre></div> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">w[z] == Divide[Subscript[P, (n)^(2)+ 1][\[Zeta]],Subscript[Q, (n)^(2)][\[Zeta]]]</pre></div> || Skipped - no semantic math || Skipped - no semantic math || - || -
|- style="background: #dfe6e9;"
|- style="background: #dfe6e9;"
| [https://dlmf.nist.gov/32.9.E7 32.9.E7] || [[Item:Q9394|<math>w(z;\mu,-\tfrac{1}{8},-\mu\kappa^{2},0) = 1+\kappa z^{1/2}</math>]]<br><syntaxhighlight lang="tex" style="font-size: 75%; background: inherit;" inline>w(z;\mu,-\tfrac{1}{8},-\mu\kappa^{2},0) = 1+\kappa z^{1/2}</syntaxhighlight> || <math></math> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">w(z ; mu , -(1)/(8), - mu*(kappa)^(2), 0) = 1 + kappa*(z)^(1/2)</pre></div> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">w[z ; \[Mu], -Divide[1,8], - \[Mu]*\[Kappa]^(2), 0] == 1 + \[Kappa]*(z)^(1/2)</pre></div> || Skipped - no semantic math || Skipped - no semantic math || - || -
| [https://dlmf.nist.gov/32.9.E7 32.9.E7] || <math qid="Q9394">w(z;\mu,-\tfrac{1}{8},-\mu\kappa^{2},0) = 1+\kappa z^{1/2}</math><br><syntaxhighlight lang="tex" style="font-size: 75%; background: inherit;" inline>w(z;\mu,-\tfrac{1}{8},-\mu\kappa^{2},0) = 1+\kappa z^{1/2}</syntaxhighlight> || <math></math> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">w(z ; mu , -(1)/(8), - mu*(kappa)^(2), 0) = 1 + kappa*(z)^(1/2)</pre></div> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">w[z ; \[Mu], -Divide[1,8], - \[Mu]*\[Kappa]^(2), 0] == 1 + \[Kappa]*(z)^(1/2)</pre></div> || Skipped - no semantic math || Skipped - no semantic math || - || -
|-  
|-  
| [https://dlmf.nist.gov/32.9.E8 32.9.E8] || [[Item:Q9395|<math>w(z;0,0,\mu,-\tfrac{1}{2}\mu^{2}) = \kappa\exp@{\mu z}</math>]]<br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>w(z;0,0,\mu,-\tfrac{1}{2}\mu^{2}) = \kappa\exp@{\mu z}</syntaxhighlight> || <math></math> || <syntaxhighlight lang=mathematica>w(z ; 0 , 0 , mu , -(1)/(2)*(mu)^(2)) = kappa*exp(mu*z)</syntaxhighlight> || <syntaxhighlight lang=mathematica>w[z ; 0 , 0 , \[Mu], -Divide[1,2]*\[Mu]^(2)] == \[Kappa]*Exp[\[Mu]*z]</syntaxhighlight> || Translation Error || Translation Error || - || -
| [https://dlmf.nist.gov/32.9.E8 32.9.E8] || <math qid="Q9395">w(z;0,0,\mu,-\tfrac{1}{2}\mu^{2}) = \kappa\exp@{\mu z}</math><br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>w(z;0,0,\mu,-\tfrac{1}{2}\mu^{2}) = \kappa\exp@{\mu z}</syntaxhighlight> || <math></math> || <syntaxhighlight lang=mathematica>w(z ; 0 , 0 , mu , -(1)/(2)*(mu)^(2)) = kappa*exp(mu*z)</syntaxhighlight> || <syntaxhighlight lang=mathematica>w[z ; 0 , 0 , \[Mu], -Divide[1,2]*\[Mu]^(2)] == \[Kappa]*Exp[\[Mu]*z]</syntaxhighlight> || Translation Error || Translation Error || - || -
|- style="background: #dfe6e9;"
|- style="background: #dfe6e9;"
| [https://dlmf.nist.gov/32.9.E9 32.9.E9] || [[Item:Q9396|<math>\mspace{17.0mu }(\alpha,\beta,\gamma) = (\tfrac{1}{2}\mu^{2},-\tfrac{1}{8}(2n-1)^{2},-1)</math>]]<br><syntaxhighlight lang="tex" style="font-size: 75%; background: inherit;" inline>\mspace{17.0mu }(\alpha,\beta,\gamma) = (\tfrac{1}{2}\mu^{2},-\tfrac{1}{8}(2n-1)^{2},-1)</syntaxhighlight> || <math></math> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">(alpha , beta , gamma) = ((1)/(2)*(mu)^(2), -(1)/(8)*(2*n - 1)^(2), - 1)</pre></div> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">(\[Alpha], \[Beta], \[Gamma]) == (Divide[1,2]*\[Mu]^(2), -Divide[1,8]*(2*n - 1)^(2), - 1)</pre></div> || Skipped - no semantic math || Skipped - no semantic math || - || -
| [https://dlmf.nist.gov/32.9.E9 32.9.E9] || <math qid="Q9396">\mspace{17.0mu }(\alpha,\beta,\gamma) = (\tfrac{1}{2}\mu^{2},-\tfrac{1}{8}(2n-1)^{2},-1)</math><br><syntaxhighlight lang="tex" style="font-size: 75%; background: inherit;" inline>\mspace{17.0mu }(\alpha,\beta,\gamma) = (\tfrac{1}{2}\mu^{2},-\tfrac{1}{8}(2n-1)^{2},-1)</syntaxhighlight> || <math></math> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">(alpha , beta , gamma) = ((1)/(2)*(mu)^(2), -(1)/(8)*(2*n - 1)^(2), - 1)</pre></div> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">(\[Alpha], \[Beta], \[Gamma]) == (Divide[1,2]*\[Mu]^(2), -Divide[1,8]*(2*n - 1)^(2), - 1)</pre></div> || Skipped - no semantic math || Skipped - no semantic math || - || -
|- style="background: #dfe6e9;"
|- style="background: #dfe6e9;"
| [https://dlmf.nist.gov/32.9.E10 32.9.E10] || [[Item:Q9397|<math>\mspace{5.0mu }(\alpha,\beta,\gamma) = (\tfrac{1}{8}(2n-1)^{2},-\tfrac{1}{2}\mu^{2},1)</math>]]<br><syntaxhighlight lang="tex" style="font-size: 75%; background: inherit;" inline>\mspace{5.0mu }(\alpha,\beta,\gamma) = (\tfrac{1}{8}(2n-1)^{2},-\tfrac{1}{2}\mu^{2},1)</syntaxhighlight> || <math></math> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">(alpha , beta , gamma) = ((1)/(8)*(2*n - 1)^(2), -(1)/(2)*(mu)^(2), 1)</pre></div> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">(\[Alpha], \[Beta], \[Gamma]) == (Divide[1,8]*(2*n - 1)^(2), -Divide[1,2]*\[Mu]^(2), 1)</pre></div> || Skipped - no semantic math || Skipped - no semantic math || - || -
| [https://dlmf.nist.gov/32.9.E10 32.9.E10] || <math qid="Q9397">\mspace{5.0mu }(\alpha,\beta,\gamma) = (\tfrac{1}{8}(2n-1)^{2},-\tfrac{1}{2}\mu^{2},1)</math><br><syntaxhighlight lang="tex" style="font-size: 75%; background: inherit;" inline>\mspace{5.0mu }(\alpha,\beta,\gamma) = (\tfrac{1}{8}(2n-1)^{2},-\tfrac{1}{2}\mu^{2},1)</syntaxhighlight> || <math></math> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">(alpha , beta , gamma) = ((1)/(8)*(2*n - 1)^(2), -(1)/(2)*(mu)^(2), 1)</pre></div> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">(\[Alpha], \[Beta], \[Gamma]) == (Divide[1,8]*(2*n - 1)^(2), -Divide[1,2]*\[Mu]^(2), 1)</pre></div> || Skipped - no semantic math || Skipped - no semantic math || - || -
|- style="background: #dfe6e9;"
|- style="background: #dfe6e9;"
| [https://dlmf.nist.gov/32.9.E11 32.9.E11] || [[Item:Q9398|<math>w(z) = \ifrac{P_{n^{2}-n+1}(\zeta)}{Q_{n^{2}-n}(\zeta)}</math>]]<br><syntaxhighlight lang="tex" style="font-size: 75%; background: inherit;" inline>w(z) = \ifrac{P_{n^{2}-n+1}(\zeta)}{Q_{n^{2}-n}(\zeta)}</syntaxhighlight> || <math></math> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">w(z) = (P[(n)^(2)- n + 1](zeta))/(Q[(n)^(2)- n](zeta))</pre></div> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">w[z] == Divide[Subscript[P, (n)^(2)- n + 1][\[Zeta]],Subscript[Q, (n)^(2)- n][\[Zeta]]]</pre></div> || Skipped - no semantic math || Skipped - no semantic math || - || -
| [https://dlmf.nist.gov/32.9.E11 32.9.E11] || <math qid="Q9398">w(z) = \ifrac{P_{n^{2}-n+1}(\zeta)}{Q_{n^{2}-n}(\zeta)}</math><br><syntaxhighlight lang="tex" style="font-size: 75%; background: inherit;" inline>w(z) = \ifrac{P_{n^{2}-n+1}(\zeta)}{Q_{n^{2}-n}(\zeta)}</syntaxhighlight> || <math></math> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">w(z) = (P[(n)^(2)- n + 1](zeta))/(Q[(n)^(2)- n](zeta))</pre></div> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">w[z] == Divide[Subscript[P, (n)^(2)- n + 1][\[Zeta]],Subscript[Q, (n)^(2)- n][\[Zeta]]]</pre></div> || Skipped - no semantic math || Skipped - no semantic math || - || -
|- style="background: #dfe6e9;"
|- style="background: #dfe6e9;"
| [https://dlmf.nist.gov/32.9.E13 32.9.E13] || [[Item:Q9400|<math>w(z;\tfrac{1}{2}\kappa^{2},-\tfrac{1}{2}\kappa^{2},\tfrac{1}{2}\mu^{2},\tfrac{1}{2}(1-\mu^{2})) = z^{1/2}</math>]]<br><syntaxhighlight lang="tex" style="font-size: 75%; background: inherit;" inline>w(z;\tfrac{1}{2}\kappa^{2},-\tfrac{1}{2}\kappa^{2},\tfrac{1}{2}\mu^{2},\tfrac{1}{2}(1-\mu^{2})) = z^{1/2}</syntaxhighlight> || <math></math> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">w(z ;(1)/(2)*(kappa)^(2), -(1)/(2)*(kappa)^(2),(1)/(2)*(mu)^(2),(1)/(2)*(1 - (mu)^(2))) = (z)^(1/2)</pre></div> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">w[z ;Divide[1,2]*\[Kappa]^(2), -Divide[1,2]*\[Kappa]^(2),Divide[1,2]*\[Mu]^(2),Divide[1,2]*(1 - \[Mu]^(2))] == (z)^(1/2)</pre></div> || Skipped - no semantic math || Skipped - no semantic math || - || -
| [https://dlmf.nist.gov/32.9.E13 32.9.E13] || <math qid="Q9400">w(z;\tfrac{1}{2}\kappa^{2},-\tfrac{1}{2}\kappa^{2},\tfrac{1}{2}\mu^{2},\tfrac{1}{2}(1-\mu^{2})) = z^{1/2}</math><br><syntaxhighlight lang="tex" style="font-size: 75%; background: inherit;" inline>w(z;\tfrac{1}{2}\kappa^{2},-\tfrac{1}{2}\kappa^{2},\tfrac{1}{2}\mu^{2},\tfrac{1}{2}(1-\mu^{2})) = z^{1/2}</syntaxhighlight> || <math></math> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">w(z ;(1)/(2)*(kappa)^(2), -(1)/(2)*(kappa)^(2),(1)/(2)*(mu)^(2),(1)/(2)*(1 - (mu)^(2))) = (z)^(1/2)</pre></div> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">w[z ;Divide[1,2]*\[Kappa]^(2), -Divide[1,2]*\[Kappa]^(2),Divide[1,2]*\[Mu]^(2),Divide[1,2]*(1 - \[Mu]^(2))] == (z)^(1/2)</pre></div> || Skipped - no semantic math || Skipped - no semantic math || - || -
|}
|}
</div>
</div>

Latest revision as of 12:13, 28 June 2021


DLMF Formula Constraints Maple Mathematica Symbolic
Maple
Symbolic
Mathematica
Numeric
Maple
Numeric
Mathematica
32.9.E1 w ( z ; μ , 0 , 0 , - μ κ 3 ) = κ z 1 / 3 𝑤 𝑧 𝜇 0 0 𝜇 superscript 𝜅 3 𝜅 superscript 𝑧 1 3 {\displaystyle{\displaystyle w(z;\mu,0,0,-\mu\kappa^{3})=\kappa z^{1/3}}}
w(z;\mu,0,0,-\mu\kappa^{3}) = \kappa z^{1/3}

w(z ; mu , 0 , 0 , - mu*(kappa)^(3)) = kappa*(z)^(1/3)
w[z ; \[Mu], 0 , 0 , - \[Mu]*\[Kappa]^(3)] == \[Kappa]*(z)^(1/3)
Skipped - no semantic math Skipped - no semantic math - -
32.9.E2 w ( z ; 0 , - 2 κ , 0 , 4 κ μ - λ 2 ) = z ( κ ( ln z ) 2 + λ ln z + μ ) 𝑤 𝑧 0 2 𝜅 0 4 𝜅 𝜇 superscript 𝜆 2 𝑧 𝜅 superscript 𝑧 2 𝜆 𝑧 𝜇 {\displaystyle{\displaystyle w(z;0,-2\kappa,0,4\kappa\mu-\lambda^{2})=z(\kappa% (\ln z)^{2}+\lambda\ln z+\mu)}}
w(z;0,-2\kappa,0,4\kappa\mu-\lambda^{2}) = z(\kappa(\ln@@{z})^{2}+\lambda\ln@@{z}+\mu)

w(z ; 0 , - 2*kappa(,)*0 , 4*kappa(mu)- (lambda)^(2)) = z*((kappa(ln(z)))^(2)+ lambda*ln(z)+ mu)
w[z ; 0 , - 2*\[Kappa][,]*0 , 4*\[Kappa][Mu]- \[Lambda]^(2)] == z*((\[Kappa][Log[z]])^(2)+ \[Lambda]*Log[z]+ \[Mu])
Translation Error Translation Error - -
32.9.E3 w ( z ; - ν 2 λ , 0 , ν 2 ( λ 2 - 4 κ μ ) , 0 ) = z ν - 1 κ z 2 ν + λ z ν + μ 𝑤 𝑧 superscript 𝜈 2 𝜆 0 superscript 𝜈 2 superscript 𝜆 2 4 𝜅 𝜇 0 superscript 𝑧 𝜈 1 𝜅 superscript 𝑧 2 𝜈 𝜆 superscript 𝑧 𝜈 𝜇 {\displaystyle{\displaystyle w(z;-\nu^{2}\lambda,0,\nu^{2}(\lambda^{2}-4\kappa% \mu),0)=\dfrac{z^{\nu-1}}{\kappa z^{2\nu}+\lambda z^{\nu}+\mu}}}
w(z;-\nu^{2}\lambda,0,\nu^{2}(\lambda^{2}-4\kappa\mu),0) = \dfrac{z^{\nu-1}}{\kappa z^{2\nu}+\lambda z^{\nu}+\mu}

w(z ; - (nu)^(2)* lambda , 0 , (nu)^(2)*((lambda)^(2)- 4*kappa*mu), 0) = ((z)^(nu - 1))/(kappa*(z)^(2*nu)+ lambda*(z)^(nu)+ mu)
w[z ; - \[Nu]^(2)* \[Lambda], 0 , \[Nu]^(2)*(\[Lambda]^(2)- 4*\[Kappa]*\[Mu]), 0] == Divide[(z)^(\[Nu]- 1),\[Kappa]*(z)^(2*\[Nu])+ \[Lambda]*(z)^\[Nu]+ \[Mu]]
Skipped - no semantic math Skipped - no semantic math - -
32.9.E4 β = 2 n 𝛽 2 𝑛 {\displaystyle{\displaystyle\beta=2n}}
\beta = 2n

beta = 2*n
\[Beta] == 2*n
Skipped - no semantic math Skipped - no semantic math - -
32.9.E5 w ( z ) = P n 2 + 1 ( ζ ) / Q n 2 ( ζ ) 𝑤 𝑧 subscript 𝑃 superscript 𝑛 2 1 𝜁 subscript 𝑄 superscript 𝑛 2 𝜁 {\displaystyle{\displaystyle w(z)=\ifrac{P_{n^{2}+1}(\zeta)}{Q_{n^{2}}(\zeta)}}}
w(z) = \ifrac{P_{n^{2}+1}(\zeta)}{Q_{n^{2}}(\zeta)}

w(z) = (P[(n)^(2)+ 1](zeta))/(Q[(n)^(2)](zeta))
w[z] == Divide[Subscript[P, (n)^(2)+ 1][\[Zeta]],Subscript[Q, (n)^(2)][\[Zeta]]]
Skipped - no semantic math Skipped - no semantic math - -
32.9.E7 w ( z ; μ , - 1 8 , - μ κ 2 , 0 ) = 1 + κ z 1 / 2 𝑤 𝑧 𝜇 1 8 𝜇 superscript 𝜅 2 0 1 𝜅 superscript 𝑧 1 2 {\displaystyle{\displaystyle w(z;\mu,-\tfrac{1}{8},-\mu\kappa^{2},0)=1+\kappa z% ^{1/2}}}
w(z;\mu,-\tfrac{1}{8},-\mu\kappa^{2},0) = 1+\kappa z^{1/2}

w(z ; mu , -(1)/(8), - mu*(kappa)^(2), 0) = 1 + kappa*(z)^(1/2)
w[z ; \[Mu], -Divide[1,8], - \[Mu]*\[Kappa]^(2), 0] == 1 + \[Kappa]*(z)^(1/2)
Skipped - no semantic math Skipped - no semantic math - -
32.9.E8 w ( z ; 0 , 0 , μ , - 1 2 μ 2 ) = κ exp ( μ z ) 𝑤 𝑧 0 0 𝜇 1 2 superscript 𝜇 2 𝜅 𝜇 𝑧 {\displaystyle{\displaystyle w(z;0,0,\mu,-\tfrac{1}{2}\mu^{2})=\kappa\exp\left% (\mu z\right)}}
w(z;0,0,\mu,-\tfrac{1}{2}\mu^{2}) = \kappa\exp@{\mu z}

w(z ; 0 , 0 , mu , -(1)/(2)*(mu)^(2)) = kappa*exp(mu*z)
w[z ; 0 , 0 , \[Mu], -Divide[1,2]*\[Mu]^(2)] == \[Kappa]*Exp[\[Mu]*z]
Translation Error Translation Error - -
32.9.E9 ( α , β , γ ) = ( 1 2 μ 2 , - 1 8 ( 2 n - 1 ) 2 , - 1 ) 𝛼 𝛽 𝛾 1 2 superscript 𝜇 2 1 8 superscript 2 𝑛 1 2 1 {\displaystyle{\displaystyle\mspace{17.0mu }(\alpha,\beta,\gamma)=(\tfrac{1}{2% }\mu^{2},-\tfrac{1}{8}(2n-1)^{2},-1)}}
\mspace{17.0mu }(\alpha,\beta,\gamma) = (\tfrac{1}{2}\mu^{2},-\tfrac{1}{8}(2n-1)^{2},-1)

(alpha , beta , gamma) = ((1)/(2)*(mu)^(2), -(1)/(8)*(2*n - 1)^(2), - 1)
(\[Alpha], \[Beta], \[Gamma]) == (Divide[1,2]*\[Mu]^(2), -Divide[1,8]*(2*n - 1)^(2), - 1)
Skipped - no semantic math Skipped - no semantic math - -
32.9.E10 ( α , β , γ ) = ( 1 8 ( 2 n - 1 ) 2 , - 1 2 μ 2 , 1 ) 𝛼 𝛽 𝛾 1 8 superscript 2 𝑛 1 2 1 2 superscript 𝜇 2 1 {\displaystyle{\displaystyle\mspace{5.0mu }(\alpha,\beta,\gamma)=(\tfrac{1}{8}% (2n-1)^{2},-\tfrac{1}{2}\mu^{2},1)}}
\mspace{5.0mu }(\alpha,\beta,\gamma) = (\tfrac{1}{8}(2n-1)^{2},-\tfrac{1}{2}\mu^{2},1)

(alpha , beta , gamma) = ((1)/(8)*(2*n - 1)^(2), -(1)/(2)*(mu)^(2), 1)
(\[Alpha], \[Beta], \[Gamma]) == (Divide[1,8]*(2*n - 1)^(2), -Divide[1,2]*\[Mu]^(2), 1)
Skipped - no semantic math Skipped - no semantic math - -
32.9.E11 w ( z ) = P n 2 - n + 1 ( ζ ) / Q n 2 - n ( ζ ) 𝑤 𝑧 subscript 𝑃 superscript 𝑛 2 𝑛 1 𝜁 subscript 𝑄 superscript 𝑛 2 𝑛 𝜁 {\displaystyle{\displaystyle w(z)=\ifrac{P_{n^{2}-n+1}(\zeta)}{Q_{n^{2}-n}(% \zeta)}}}
w(z) = \ifrac{P_{n^{2}-n+1}(\zeta)}{Q_{n^{2}-n}(\zeta)}

w(z) = (P[(n)^(2)- n + 1](zeta))/(Q[(n)^(2)- n](zeta))
w[z] == Divide[Subscript[P, (n)^(2)- n + 1][\[Zeta]],Subscript[Q, (n)^(2)- n][\[Zeta]]]
Skipped - no semantic math Skipped - no semantic math - -
32.9.E13 w ( z ; 1 2 κ 2 , - 1 2 κ 2 , 1 2 μ 2 , 1 2 ( 1 - μ 2 ) ) = z 1 / 2 𝑤 𝑧 1 2 superscript 𝜅 2 1 2 superscript 𝜅 2 1 2 superscript 𝜇 2 1 2 1 superscript 𝜇 2 superscript 𝑧 1 2 {\displaystyle{\displaystyle w(z;\tfrac{1}{2}\kappa^{2},-\tfrac{1}{2}\kappa^{2% },\tfrac{1}{2}\mu^{2},\tfrac{1}{2}(1-\mu^{2}))=z^{1/2}}}
w(z;\tfrac{1}{2}\kappa^{2},-\tfrac{1}{2}\kappa^{2},\tfrac{1}{2}\mu^{2},\tfrac{1}{2}(1-\mu^{2})) = z^{1/2}

w(z ;(1)/(2)*(kappa)^(2), -(1)/(2)*(kappa)^(2),(1)/(2)*(mu)^(2),(1)/(2)*(1 - (mu)^(2))) = (z)^(1/2)
w[z ;Divide[1,2]*\[Kappa]^(2), -Divide[1,2]*\[Kappa]^(2),Divide[1,2]*\[Mu]^(2),Divide[1,2]*(1 - \[Mu]^(2))] == (z)^(1/2)
Skipped - no semantic math Skipped - no semantic math - -